Prevention and Detection of Phantom Billing in Health Insurance: A Literature Review - Syafrina Ulfah (Jurnal Kebijakan Kesehatan Indonesia, 2026)
Fraud, particularly phantom billing in health insurance programs, still occurs in Indonesia despite the existence of regulations related to its prevention and handling. Therefore, new methods are needed to overcome phantom billing. This study aims to analyze methods for preventing and detecting phantom billing in health insurance through a literature review. Articles were searched for in the Scopus, PubMed, ScienceDirect, ProQuest, and Google Scholar databases, using the keywords “fraud prevention” AND “fraud detection” AND “phantom billing” AND “health insurance”. The inclusion criteria for this study included all articles available in open access full text, published between 2020 and 2025, and discussing the prevention and detection of phantom billing in health insurance. Articles in the form of reviews, not in English or Indonesian, and irrelevant articles were excluded from this study. The screening results yielded 19 articles for review in this study. There are various methods of preventing and detecting phantom billing that can be used, but no single method is effective; rather, a combination of technology-based and governance strategies is needed. The results of the study recommend a hybrid approach that combines technological innovation, strong regulation, and strict supervision so that the practice and losses caused by phantom billing do not occur again.